Arquitectura: institución, museo e identidad - Cumpa González, Luis (2023)
Understanding architecture from the concept of an institution can help determine the character of buildings. Conceiving the city as a meeting place for institutions is what leads to recognizing the value of these institutions as dynamizers of the city to the extent that, in addition to functioning as a guiding element (landmark), it can also give it a symbolic character. (monumentality) and, therefore, requires architects and urban planners to consider its fundamental presence when initiating the intervention of the urban space. The concepts of monumentality, landmark, meeting and character come together in the design process along with the institution to understand that architecture is a totality in the action of human beings’ habitation. This totality is what will shape what we consider the identity of the architectural project, which is what this article aims to explain.